Occupational Health and Safety, Training, and Teamwork for Hospital Medical Performance - Khalimatus Sa’diyah (Inovasi Analisis Data, 2024)
Objective: This study aims to investigate the relationships between Occupational Health and Safety (OHS), Training, Teamwork, and medical personnel performance in hospital settings.Method: Data were collected from medical personnel in various hospitals, and multiple regression analysis was employed to examine the associations between OHS, Training, Teamwork, and medical personnel performance. Additionally, multicollinearity tests and Normal P-Plot Regression Standardized Residual analysis were conducted to ensure the reliability of the findings.Findings: The results indicate significant positive relationships between OHS, Training, Teamwork, and medical personnel performance. Specifically, conducive OHS environments, effective training programs, and collaborative teamwork dynamics were found to enhance medical personnel performance significantly.Novelty: This study contributes to the existing literature by providing empirical evidence of the importance of OHS, Training, and Teamwork in improving medical personnel performance. The findings underscore the critical role of these factors in optimizing healthcare delivery and patient outcomes.Research Implications: The findings suggest that healthcare organizations should prioritize creating safe and healthy work environments, investing in comprehensive training programs, and fostering effective teamwork practices to enhance medical personnel performance. These implications have significant implications for improving operational efficiency and patient care quality in healthcare settings